Answer:
[tex]f(6) = f(-6)[/tex] --- True
[tex]f(6)=2 * f(3)[/tex] --- False
Step-by-step explanation:
Given
[tex]f(x) = \frac{x^2}{3} - 2[/tex]
Solving (a): f(6) = f(-6)
First, we solve for f(6) by substituting 6 for x in [tex]f(x) = \frac{x^2}{3} - 2[/tex]
[tex]f(6) = \frac{6^2}{3} - 2[/tex]
[tex]f(6) = \frac{36}{3} - 2[/tex]
[tex]f(6) = 12 - 2[/tex]
[tex]f(6) = 10[/tex]
Next, we solve for f(-6) by substituting -6 for x in [tex]f(x) = \frac{x^2}{3} - 2[/tex]
[tex]f(-6) = \frac{-6^2}{3} - 2[/tex]
[tex]f(-6) = \frac{36}{3} - 2[/tex]
[tex]f(-6) = 12 - 2[/tex]
[tex]f(-6) = 10[/tex]
We have that:
[tex]f(6) = f(-6) = 10[/tex]
Hence, the statement is true
Solving (b): [tex]f(6)=2 * f(3)[/tex]
We have that:
[tex]f(6) = 10[/tex]
Next, we solve for f(3) by substituting 3 for x in [tex]f(x) = \frac{x^2}{3} - 2[/tex]
[tex]f(3) = \frac{3^2}{3} - 2[/tex]
[tex]f(3) = \frac{9}{3} - 2[/tex]
[tex]f(3) = 3 - 2[/tex]
[tex]f(3) = 1[/tex]
[tex]2 * f(3) = 2 * 1[/tex]
[tex]2 * f(3) = 2[/tex]
So:
[tex]f(6)=2 * f(3)[/tex]
[tex]10 \neq 2[/tex]
Hence, the statement is false